2005
DOI: 10.1016/j.appet.2005.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the number of repellent-treated and untreated food or water containers on intake by the European starling

Abstract: The availability of multiple sources of food and drink has a profound influence on choice behavior in rodents. It is not known how other taxa might respond to the same kind of variation in availability. We tested European starlings (Sturnus vulgaris) with various combinations of unadulterated and repellent-treated (0.025% citronellyl acetate) resources. In Experiment 1, birds drank more plain than repellent-treated water than when given (a) 2 bottles of plain water and 2 of repellent-water, or (b) 3 bottles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Tordoff's mouse studies revealed greater intake of alcohol [44] and other taste solutions [45] when extra bottles were offered. The number of fluid sources influenced starlings' intake in a study of chemical repellents [14]. Rats given four cups of standard chow ate more than those given only one, but intakes were equal in other groups given one or four cups of high-fat chow [25].…”
Section: Number Of Sourcesmentioning
confidence: 99%
“…Tordoff's mouse studies revealed greater intake of alcohol [44] and other taste solutions [45] when extra bottles were offered. The number of fluid sources influenced starlings' intake in a study of chemical repellents [14]. Rats given four cups of standard chow ate more than those given only one, but intakes were equal in other groups given one or four cups of high-fat chow [25].…”
Section: Number Of Sourcesmentioning
confidence: 99%
“…Some species such as starlings are also agricultural pests; both pure and applied research on these species is therefore important for understanding when they will choose not to eat specifi c foods and for the development and testing of potential avian repellents (Hile 2004;Hile and Tordoff 2005;Skelhorn and Rowe 2009). …”
Section: Foragingmentioning
confidence: 99%